How do students’ learning goals differ? A text mining approach to reveal the individual differences - Ng, Hilary K. Y. (Frontiers in Education, 2024)
Extensive research has demonstrated that setting learning goals could benefit academic performance, learning motivation, and attendance rate. The current research further focused on the content of learning goals with the text mining approach. This research uncovered three main differences between high-achieving students and their counterparts. Specifically, high-achieving students exhibited a higher tendency to devise goals aligning with the course objectives. They were more driven by their desire for academic excellence and personal growth. Lastly, they expressed themselves with higher linguistic alignment with the context. This research enriched the understanding of the characteristics of learning goals and provided practical implications for educators to develop a more inclusive and supportive learning environment that address diverse student needs.